(untitled) (The Review of Diabetic Studies, 2025)
The healthcare field contains various specialists that come together to provide comprehensive care to the patients nationwide. This research paper focuses on the three core healthcare specializations: the Paramedic, Radiology Specialist, and the Respiratory Therapist. These three specializations provide the modern health care systems with significant contributions to patient diagnosis and treatment while also providing emergency care. This paper aims to provide the contributions of the various specialists to the modern health care systems by analyzing the respective fields of each healthcare specialization and in addition to that, the author also focuses on the educational backgrounds, professional duties, technological usage, challenges, and prospects. This research paper uses professional reports, literature, and research studies to provide a detailed view of the health care specializations that are the core of the modern health care systems.